Grain refinement of Mg-Al magnesium alloys by carbon inoculation - 王朝辉 康永林 赵鸿金 徐跃 (Transactions of Nonferrous Metals Society of China, 2006)
C2Cl6 was used as grain refiner for AM60 magnesium alloys. The effects of grain refinement process on chemical ＂,omposition, microstructure, impact energy, hardness and mechanical properties of magnesium alloys were investigated with XRF spectrometer, optical and electronic microscopes, pendulum impact tester, hardness tester and MTS material testing machine. The results show that C2Cl6 has good effects on microstructure and mechanical properties of AM60 magnesium alloys. The optimum usage of C2Cl6 in AM60 for getting the best properties is 1.0%. The results of electronic microscopic examination and theoretical analyses show that Al4C3 should be the potent heterogeneous nucleant for Mg-AI magnesium alloys.